Morality, Technology, and Enjoyment: Meta Analyzing the Enjoyment of Mediated Violence. Issue 4 (8th August 2022) - Rasul, Azmat; Shin, Donghee
ABSTRACT: This meta-analysis addressed the effects of mediated violence on the enjoyment audiences experienced after exposure to a diverse array of entertainment programs. Published journal articles were collected and effect sizes were analyzed to examine if there were differences in the enjoyment of violent content. Through the lens of a fixed effects model, the results indicated that the morality of audiences and nature of visual media did not impact enjoyment of violence and the selected experiments shared a statistically significant common effect size ( d = 0.33). Although synthesized data signified a fairly homogeneous effect of mediated violence on enjoyment, the experiments employing morality and video games as moderators were heterogeneous. The current study offered guidelines for further inquiry to explicate the nature of heterogeneity and generalizability of the study results.